Plataforma web para el acompañamiento pedagógico virtual en instituciones educativas públicas polidocentes del nivel secundario en Lima Metropolitana - Carpio Salas, Lindsey Cheryl (2024)
For many years, the Peruvian educational system has been characterized by low educational achievement, one of the reasons being the inadequate performance of teachers for student learning. For this reason, the Ministry of Education implemented the strategy of Pedagogical Accompaniment, whose main objective is to strengthen the performance of teachers and thus help optimize student learning. Therefore, the pedagogical accompaniment has shown through the evidence collected that, progressively, the academic level of the students has improved in the different pedagogical spaces of the Educational Institutions that have benefited from this strategy; however, low educational achievements persist in those areas that have not benefited from pedagogical accompaniment, therefore, the problem related to the limited coverage of the Pedagogical Accompaniment strategy in Educational Institutions was identified, likewise, considering the complexity of the problem and the delimited resources, the research carried out has been oriented in the public full grade Educational Institutions of the secondary level in Metropolitan Lima in the period 2017 - 2019. In this sense, upon analyzing the main causes of the aforementioned problem, the main one selected was the inadequate targeting applied to the Educational Institutions (IIEE), with respect to which the present innovation project has been developed; the purpose of which is to increase the coverage of the Educational Institutions that require pedagogical accompaniment, not requiring a larger budget for its implementation. The innovation project consists of the implementation of the virtual Pedagogical Accompaniment, through a web platform that allows the development of the following modalities: classroom visits, GIAs (Inter-learning groups), updating workshops, pedagogical advisories and courses; for which, cameras will be used for the recording of classes, storage in the platform, and subsequent feedback to teachers by the pedagogical accompaniers.